Current status of application of digital technologies in plantation crops - Hebbar, K. B.; Bhat, Ravi (Indian Horticulture, 2025)
The plantation sector in India, comprising crops like coconut, arecanut, tea, coffee, rubber, and oil palm, significantly contributes to the national economy, supporting over 30 million small-scale growers. Despite its importance, the sector faces challenges in resource management, labour shortages, and environmental sustainability. The integration of digital technologies such as IoT, AI, drones, and blockchain is revolutionizing plantation crop management. These technologies enhance resource efficiency, facilitate precise crop monitoring, predict yields, detect diseases, and improve pest control. Additionally, AI-driven tools and big data analytics aid in optimizing irrigation, fertilization, and market strategies. Drones offer advantages in aerial surveys and pesticide application, while blockchain ensures transparency in the supply chain, especially for export-oriented crops. The collaborative efforts between agricultural and technological sectors are paving the way for a more sustainable, efficient, and competitive plantation industry. This integration is crucial for addressing resource limitations and ensuring long-term growth and global market competitiveness in the plantation sector.